Influence of dates of Sowing on Quality and Yield Potential in Rabi Sorghum Genotypes - V., Chaithra; Uppar, D. S.; B. O., Kiran (International Journal of Bio-resource and Stress Management, 2017)
Sorghum is predominantly grown under rainfed conditions, subjected to many biotic and abiotic stresses which are influenced by weather. Weather aberrations during crop growth and development results in drastic reduction in yield and quality. The time of sowing is one important decisive factor that has direct bearing on weather conditions, the crop encounter. Hence, the field experiment was conducted to evaluate the sorghum genotypes for cold tolerance under varied dates of sowing. The quality parameters such as seed germination, seedling shoot and root length, seedling dry weight and vigour index differed significantly with dates and genotypes. Standard germination (92.60 %), root length (15.22 cm), seedling vigour index (3,372) and seedling dry weight (15.94 mg) were observed significantly higher under the September 30th sowing compared to other dates of sowing. Among the genotypes significantly higher seed yield was recorded in genotype BJV-44 (1317 kg ha-1) and 39th standard week recorded maximum seed yield (1378 kg ha-1) followed by 41st (1212 kg ha-1). The influence of temperature had a greater impact on seed yield in genotype BJV-44 i.ewhen lower temperature (29.60 °C) coincided with the reproductive phase. Reduced seed set per cent was observed under 52nd standard week (72.93%). However, temperature fluctuations (> 29.30/13.60 oC) favoured higher pollen fertility under delayed condition (S6). The experiment suggested that, critical temperatures during the pre and post anthesis period of sorghum has a greater impact on seed set per cent and pollen fertility that contributes to the total grain yield in sorghum.